2006
DOI: 10.1128/jvi.80.8.4174-4178.2006
|View full text |Cite
|
Sign up to set email alerts
|

Role of Endosomal Cathepsins in Entry Mediated by the Ebola Virus Glycoprotein

Abstract: Using chemical inhibitors and small interfering RNA (siRNA), we have confirmed roles for cathepsin B (CatB) and cathepsin L (CatL) in Ebola virus glycoprotein (GP)-mediated infection. Treatment of Ebola virus GP pseudovirions with CatB and CatL converts GP1 from a 130-kDa to a 19-kDa species. Virus with 19-kDa GP1 displays significantly enhanced infection and is largely resistant to the effects of the CatB inhibitor and siRNA, but it still requires a low-pH-dependent endosomal/lysosomal function. These and oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

25
611
4
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 393 publications
(642 citation statements)
references
References 22 publications
25
611
4
2
Order By: Relevance
“…Medina et al (53) have observed that a Zaire ebolavirus GP 1,2 lacking residues 241-496 nonetheless retained its ability to mediate entry of a pseudotyped retrovirus. (18,21).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Medina et al (53) have observed that a Zaire ebolavirus GP 1,2 lacking residues 241-496 nonetheless retained its ability to mediate entry of a pseudotyped retrovirus. (18,21).…”
Section: Discussionmentioning
confidence: 99%
“…However, its deletion enhances rather than decreases the efficiency of GP 1,2 -mediated infection (13, 16 -18). Receptor binding is followed by endocytosis of the virions (19), acidification of the endocytotic vesicle (4,5,20), and proteolytic processing of GP 1 by endosomal cathepsins (18,21). Conformational changes in the filoviral GP 2 subunit facilitate lipid mixing and fusion of the viral and cellular membranes, in a sequence of steps thought similar to those mediated by orthomyxoviral and retroviral transmembrane proteins (22)(23)(24)(25).…”
mentioning
confidence: 99%
“…2). By affecting either viral entry 31,32 or exit 33,34 , these and other proteases could influence viral cellular tropisms and perhaps interactions between glycoprotein domains and antibodies (FIGS 2,3). Moreover, Barrientos and Rollin reported recently that endosomal proteolytic enzymes, including cathepsins, were released from EBOV-infected cells, that this release was more pronounced in cells infected with a more lytic variant of EBOV and that cytopathicity was diminished by the cathepsin inhibitor E64 (REF.…”
Section: Box 1 | Filovirus-disease Basicsmentioning
confidence: 99%
“…The fit curves are plotted using the corresponding open circles, X's, and open diamonds, respectively. (17,19), and EnvA is well incorporated into VSV pseudotyped particles (Z. Chen, unpublished data), We therefore assessed the fusion activity of EnvA on VSV pseudovirions. As seen with ASLV-A ( Fig.…”
mentioning
confidence: 99%